2014
DOI: 10.1083/jcb.201307116
|View full text |Cite
|
Sign up to set email alerts
|

PKA-dependent dynein switching from lysosomes to adenovirus: A novel form of host–virus competition

Abstract: PKA-mediated phosphorylation of a specific residue in the dynein light intermediate chain 1 releases the motor protein from lysosomes and late endosomes while activating its recruitment to adenovirus capsids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 59 publications
7
82
0
Order By: Relevance
“…Internalized viral particles disrupt endosomal membranes, escape into the cytosol, and are transported along microtubules to the nuclear membrane, where viral DNA is imported into the cell nucleus followed by expression of its genetic program (66). Dynein-dynactin motors are switched away from Rab7-containing late endosomes and lysosomes to viral capsids in order to initiate transport to the nucleus by a mechanism involving a direct interaction between a hexon subunit of the capsid and dynein, leading to a partial inhibition of lysosome function (68). Consistent with these findings, we showed that Ad2 infection led to a significant reduction in cholesterol transport from late endosomes and lysosomes to other organelles by a mechanism that is normally masked by RID␣ expression in cells infected with wild-type Ad2.…”
Section: Discussionmentioning
confidence: 99%
“…Internalized viral particles disrupt endosomal membranes, escape into the cytosol, and are transported along microtubules to the nuclear membrane, where viral DNA is imported into the cell nucleus followed by expression of its genetic program (66). Dynein-dynactin motors are switched away from Rab7-containing late endosomes and lysosomes to viral capsids in order to initiate transport to the nucleus by a mechanism involving a direct interaction between a hexon subunit of the capsid and dynein, leading to a partial inhibition of lysosome function (68). Consistent with these findings, we showed that Ad2 infection led to a significant reduction in cholesterol transport from late endosomes and lysosomes to other organelles by a mechanism that is normally masked by RID␣ expression in cells infected with wild-type Ad2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of pathogens on trafficking adaptor proteins have been reported as well. Salmonella displaces RILP from Rab7-containing vesicles, enhancing kinesin-dependent trafficking (8), and adenovirus induces the phosphorylation of dynein to block the RILP-dynein binding (20). In each of these cases, the Rab protein and its adaptors are targets responsible for trafficking alterations.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on automated particle detection (25-nm resolution), tracking, and motility analysis software to determine segments of constant capsid velocities (16,24) (Fig. 4; see also Materials and Methods).…”
Section: Fig 2 Pk15-mng-vp26 Cells Produce Dual-color Prv180g (A) Timentioning
confidence: 99%